What is There About DevOps Assessment? A Systematic Mapping - Orozco-Garcés, Carlos-Eduardo; Pardo-Calvache, César-Jesús; Salazar-Mondragón, Yilber-Hernán (Universidad Pedagógica y Tecnológica de Colombia, 2022)
DevOps has been established as a framework used by software development companies seeking to set mechanisms to automate their development processes. Consequently, over the last decade, many companies have adopted DevOps to support their project’s development process and perform continuous improvement tasks to ensure that it is applied correctly. To achieve this, companies are looking for solutions that allow them to evaluate the degree of implementation of DevOps in their internal processes. In this sense, the objective of this study focuses on identifying, through a systematic mapping of the literature, the mechanisms used to assess DevOps in software development companies. According to the above, the current state of knowledge related to the proposal of processes, models, techniques, tools, and methodological guides is presented to conduct the DevOps assessment. As a result, it is noted that there are multiple methodological solutions that seek to assess DevOps; however, a high degree of heterogeneity was evidenced in the identified solutions, resulting in the need to establish a clear framework that serves as the basis for proposing a generic, structured, and unambiguous DevOps assessment model applicable to software companies.